The effect of coconut shells on engineering properties of porous asphalt - Manap, Norhafizah (2015)
Properties of porous asphalt using coconut shells as substitute to aggregate is being studied. The control specimen of conventional porous asphalt and samples of porous asphalt incorporating 10%, 30% and 50% coconut shells were made. The physical properties of the coconut shells as well as the engineering properties of porous asphalt with coconut shells mixtures were investigated in the laboratory. Seven different tests were tested for each mixtures. The tests were including Marshall, Cantabro, binder drain-down, air voids, theoretical maximum density, permeability and impedance tube test. While to determine the materials properties, another four tests were conducted. They were including sieve analysis, aggregate impact value, specific gravity and water absorption test. From the investigation, it is found that the porous asphalt incorporating 10% coconut shells have pass all the parameters tested similar to conventional porous asphalt. It also shows better result for permeability and sound absorption. However, porous asphalt with 30% and 50% coconut shells shows a decrement of performance for engineering properties of porous asphalt.